Pengaruh Evaluasi Kinerja dan Motivasi Kerja Karyawan terhadap Kualitas Pelayanan Frontliner - Khairani, Nazla; Nasution, Juliana (SAFE-Network, 2023)
This study aims to determine the effect of performance evaluation and employee motivation on frontliner service quality at Bank Btn Syariah KCP Setiabudi Medan. This study used a quantitative method with a questionnaire research instrument with multiple regression analysis. The sampling method uses total sampling, with a total population of 40 employees at Bank BTN Syariah Kcp Setiabudi and a total sample of 40 employees at Bank BTN Syariah Kcp Setiabudi. The results showed that the effect of significant performance evaluation on the quality of tcount> ttable was 5.652> 1.683 and the resulting significance value was 0.000 <level of significance 0.05. This means that the effect of performance evaluation has a significant effect on frontliner service quality at Bank Btn Syariah Kcp Setiabudi Medan, and the results show that work motivation has a significant effect on service quality tcount > ttable 2.273 > 1.683 and the resulting significance value is 0.016 <significant level of 0.05. This shows that work motivation has a significant effect on the quality of Frontliner services at Bank BTN Syariah KCP Setiabudi Medan.